2013
DOI: 10.1073/pnas.1222334110
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor corepressor (NCOR1) regulates in vivo actions of a mutated thyroid hormone receptor α

Abstract: Genetic evidence from patients with mutations of the thyroid hormone receptor α gene (THRA) indicates that the dominant negative activity of mutants underlies the pathological manifestations. However, the molecular mechanisms by which TRα1 mutants exert dominant negative activity in vivo are not clear. We tested the hypothesis that the severe hypothyroidism in patients with THRA mutations is due to an inability of TRα1 mutants to properly release the nuclear corepressors (NCORs), thereby inhibiting thyroid ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 30 publications
7
32
0
Order By: Relevance
“…Utilizing NCoR⌬ID to disrupt TR-NCoR interaction partially reversed the inhibition by the mutant TR, consistent with the mutation at Lys-443 influencing the interface with NCoR. A recent study reported that the altered adipogenesis seen in TR␣PV mice was completely rescued by expression of NCoR⌬ID (61). Although the model system and the TR mutation differ from the TR sumoylation mutants that we studied, the mechanism is similar.…”
Section: Discussionsupporting
confidence: 83%
“…Utilizing NCoR⌬ID to disrupt TR-NCoR interaction partially reversed the inhibition by the mutant TR, consistent with the mutation at Lys-443 influencing the interface with NCoR. A recent study reported that the altered adipogenesis seen in TR␣PV mice was completely rescued by expression of NCoR⌬ID (61). Although the model system and the TR mutation differ from the TR sumoylation mutants that we studied, the mechanism is similar.…”
Section: Discussionsupporting
confidence: 83%
“…The results from studies performed on mutant Thra mouse models suggest that the recruitment or action of coregulators, mainly corepressors, on TRα1 could be a target for treatment in individuals with THRA mutations 13. A better understanding of the role that TRα1 coregulator dysfunction plays in this genetic syndrome is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…At peripheral level, weight loss, severe thyroid hyperplasia, and repression of a number of hepatic TR target genes were also reversed. Furthermore, expression of NCoRΔID could partially ameliorate abnormalities in the HPT axis of Thra1 PV/+ mice that carry the dominant-negative frameshift PV mutation and display a phenotype similar to that found in humans with mutations in Thra gene (Fozzatti et al 2013). NCoRΔID/Thra1 PV/+ animals also displayed improvement in severe growth retardation, infertility, delayed bone development, and impaired adipogenesis.…”
Section: Role Of Co-repressors In Rthmentioning
confidence: 63%